Trocas gasosas e morfometria de plantas de milho inoculadas com Azospirillum brasilense e fungos micorrízicos arbusculares sob adubação fosfatada - Inagaki, Adriano Mitio (2017)
The objective of this work was to analyze the development and gas exchange of maize plants under fertilization and inoculation of Azospirillum brasilense in Arbuscular Microrrimal Fungi (AMF), as well as the residual effects of A. brasilense and for the production of phosphorus in corn. Response to nitrogen fertilization. In the greenhouse, no first experiment had two corn crops. For the first cultivation use the block design with four replications, in a 2x4 factorial scheme. Inoculation of A. brasilense and control and four doses of phosphate fertilization (0; 150; 300 and 450 mg dm-3) were tested, without nitrogen fertilization. In the second harvest, a residual effect of the inoculation and P doses was obtained, obtaining the same factorial scheme (2x4) composed of the same treatments, under successive maize cultivation, with nitrogen fertilization. In the second experiment, a randomized block design was used in a 2x5 factorial scheme and four replications. The first factor was the presence and absence of phosphate fertilization and the second factor was the combination of inoculation with A. brasilense and FMA species, resulting in the following treatments: control; Inoculation of A. brasilense; A. brasilense + Acaulospora scrobiculata; A. brasilense + Claroideoglomus etunicatum; E A. brasilense + Gigaspora margarita. Similar shapes of the following variables: stem diameter, leaf number, plant length, root volume, leaf dry matter mass, stem + hem, root, leaf area and SPAD index. Also evaluated were foliar content of N and P, populations of endophytic diazotrophic bacteria in the roots and number of AMF spores in the substrate. Net assimilation rate of CO2 (A), leaf transpiration (E), stomatal conductance (gs) and internal CO2 concentration (Ci). With the results of the first experiment, the inoculation of A. brasilense on corn seeds associated with phosphate fertilization, without addition of nitrogen, resulted in a higher development of the plants at 36 days after emergence (AED). At a dose of 300 mg dm-3 of P, maize plants with nitrogen fertilizer coverage and the remaining population of A. brasilense had a positive effect in relation to the development of the crop. As a consequence of the higher content of P and leaf chlorophyll, the plants showed higher A, E, gs and Ci resulting in higher water efficiency (A/E). In the second experiment, the treatments of A. brasilense + A. scrobiculata and A. brasilense + C. etunicatum resulted in a greater accumulation of leaf N in the absence of phosphate fertilization in relation to treatment without inoculation. The inoculation with increased insulation or foliar content of P when compared to the control treatment. The use of phosphate fertilization resulted in an increase in the gas exchange and, consequently, a greater development of plants. Roots of maize plants submitted to phosphate fertilization had a higher population of diazotrophic bacteria. In the present study, the mycorrhizal spores of A. scrobiculata, C. etunicatum and G. margarita were not observed on the substrate at 30 DAE.